First record of the neotropical otter Lontra longicaudis annectens (Carnivora, Mustelidae) in the estuary Boca Negra, Jalisco, Mexico: an approach to understanding its diet. - Rodríguez-Uribe, M.C.; Rubio-Padilla, M.A.; Navarro-Rodríguez, M.C. (Revista Bio Ciencias, 2015)
The first record of the neotropical otter Lontra longicaudis annectens in the estuary Boca Negra, Jalisco, Mexico is presented. It includes relevant information about its diet and a photograph in its natural habitat is showed.